A new horned and long-necked herbivorous stem-archosaur from the Middle Triassic of India - Sengupta, Saradee (Sci Rep, 2017)
The early evolution of archosauromorphs (bird- and crocodile-line archosaurs and stem-archosaurs) represents an important case of adaptive radiation that occurred in the aftermath of the Permo-Triassic mass extinction. Here we enrich the early archosauromorph record with the description of a moderately large (3–4 m in total length), herbivorous new allokotosaurian, Shringasaurus indicus, from the early Middle Triassic of India. The most striking feature of Shringasaurus indicus is the presence of a pair of large supraorbital horns that resemble those of some ceratopsid dinosaurs. The presence of horns in the new species is dimorphic and, as occurs in horned extant bovid mammals, these structures were probably sexually selected and used as weapons in intraspecific combats. The relatively large size and unusual anatomy of Shringasaurus indicus broadens the morphological diversity of Early–Middle Triassic tetrapods and complements the understanding of the evolutionary mechanisms involved in the early archosauromorph diversification.